DESIGN AUGMENTED REALITY FOR PROPERTY IN JIARMAH GROUP - Sintia Sintia; Yonky Pernando (J-Com (Journal of Computer), 2023)
Abstract: Augmented reality is a technology that combines the virtual world and the real world in the form of two-dimensional or 3D objects in real time. This study uses the markerless augmented reality method to display the object. This study uses the prototype method where researchers listen to customers, build or revise mockups and customer test drive mockups. This augmented reality application was created using the Blender, Unity, Sketchup Pro and Vuforia SDK applications. Making three-dimensional objects is made using Blender and Sketchup Pro while making applications using Unity and Vuforia SDK. The results of the research on the application that was made were tested using blackbox testing where the test results obtained "as expected" which means the application is functioning and working properly. Keywords: augmented reality; markerless augmented reality; 3D  Abstrak: Augmented reality adalah teknologi yang mengubah realitas menjadi objek dua dimensi atau tiga dimensi secara real time. Studi ini menggunakan metode augmented reality tanpa penanda untuk mengungkap objek. Penelitian ini menggunakan metode prototipe, di mana peneliti mendengarkan pelanggan, mengembangkan atau mengubah maket, kemudian meminta pelanggan untuk menguji coba maket tersebut. Aplikasi augmented reality ini dibuat menggunakan Blender, Unity, Sketchup Pro, dan Vuforia SDK. Objek tiga dimensi dibuat menggunakan Blender dan Sketchup Pro, sedangkan aplikasinya dibuat menggunakan Unity dan Vuforia SDK. Hasil penelitian pada aplikasi yang diuji menggunakan pengujian blackbox yang mendapatkan hasil "sesuai harapan" yang memiliki arti aplikasi sudah berfungsi dan bekerja dengan baik. Kata kunci: augmented reality; markerless augmented reality; 3D